The Influence Of Digital Leadership and Work Motivation On Job Satisfaction Of Generation Z Employees In The Banking Sector In Surabaya City - Alya Nadia Zahrah; Sonja Andarini (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of digital technology encourages organizations, including the banking sector, to adapt to digital transformation in managing human resources. One of the important factors in creating employee Job Satisfaction is the implementation of Digital Leadership and the level of Work Motivation possessed by employees. Generation Z, as a generation that grows up in the digital era, has different characteristics compared to previous generations, requiring leadership that is adaptive to technology and a work environment that can enhance employee motivation. Therefore, this study aims to analyze the effect of Digital Leadership and Work Motivation on Job Satisfaction among Generation Z employees in the banking sector in Surabaya. This research employed a quantitative approach using a survey method through questionnaires distributed to 96 Generation Z employees working in the banking sector in Surabaya. The data were analyzed using multiple linear regression analysis with the asksistance of SPSS software. The results of the study indicate that Digital Leadership and Work Motivation simultaneously have a positive and significant effect on Job Satisfaction. Partially, Digital Leadership has a positive and significant effect on Job Satisfaction, while Work Motivation also has a positive and significant effect on Job Satisfaction.